Program Sosialisasi Pemberdayaan Ekonomi Kreatif dengan Pengelolaan Sampah Mandiri - Sugiyat; Miftahul Firdaus (LP3M IAIFA Kediri, 2022)
PKM is a form of service from the Mamba'ul Ulum Surakarta Islamic Institute to the community with the hope that knowledge can be enjoyed by the community as a means of social and charitable worship to Allah Subhanahu Wa Ta'ala. Therefore, it is appropriate if we participate in the implementation of this activity. Especially in this era of the Asean Economic Community, it is required not only to understand in theory, but also to be able to implement it in society. Socilasization of creative economy empowerment by providing skills and motivation for the community by managing waste into high-value commudities including: 1) Community development and empowerment by providing waste banks, 2) With these waste banks, all household and home waste can be managed and can be made into selling value commudities according to their respective types, 3) Managing household waste into organic compost, so that it can be packaged as hard compost and liquid compost, and has a high selling ratio, 4) Managing plastic waste in magic into various kinds of handicrafts from bags of clothes, brooches, coasters and various kinds of toys from used drinking water bottles, 5) Motivating the community to become POKDARWIS. Tourism Awareness Group, with a green environmental arrangement full of medicinal plants and ornamental plants and becoming a pilot village with the best waste management. The Socialization of Creative Economy Empowerment with Independent Waste Management was followed by residents and members of the PKK of Kemlaan Village, because it was still a pandemic period so that paeserta was very limited. The time limit so that the practice of making compost from household waste and souvenir products, accessories made from plastic waste is not optimal.